Klasterisasi Pemilihan Paket Umrah Berdasarkan Musim untuk Menentukan Strategi Promosi Menggunakan Algoritma K-Means - Rahayu, Ajeng; Dewi, Sofia (Jurnal Dimamu, 2024)
This research aims to classify Umrah package selection based on season using the K-Means algorithm, which is expected to help PT Pradana Grassindo Travel in determining more effective promotional strategies. The background to the problem includes problems in managing airline ticket prices and accommodation availability during the peak season, as well as extreme weather conditions in Saudi Arabia. The research method involved collecting primary data through interviews and literature study, the data obtained amounted to 149 data, which was then processed using the K-Means clustering method and using Microsoft Excel and RapidMiner software. The analysis results show that the K-Means algorithm is able to group pilgrim data into two clusters based on departure season, namely Summer and Winter. This research provides a significant contribution in improving promotional strategies and services for Umrah pilgrims.